Bekerja Bersama Berperan Setara: Kemitraan dalam Penanggulangan Abrasi di Desa Paojepe Kabupaten Wajo Propinsi Sulawesi Selatan - Oktovianus Rusmin (Antropologi Indonesia, 2005)
The environmental degradation was a major problem for people who living in the coastal area of Paojepe village. Some previous efforts to address this problem were not successful due to top-down approach and lack of community participation. Learning from the experience, a partnership between University of Indonesia, an NGO, and local community was established to address coastal abrasion by replanting mangrove. Local institutions such as kinship relations and patron-client relationship (Punggawa-Sawi) were functioned as capital in implementing the program. Awareness rising on coastal rehabilitation through local institutions can encourage people to undertake mangrove conservation. Key words: social capital; stakeholders; 'Punggawa-Sawi'.